2012
DOI: 10.1101/gr.133702.111
|View full text |Cite
|
Sign up to set email alerts
|

Human genomic disease variants: A neutral evolutionary explanation

Abstract: Many perspectives on the role of evolution in human health include nonempirical assumptions concerning the adaptive evolutionary origins of human diseases. Evolutionary analyses of the increasing wealth of clinical and population genomic data have begun to challenge these presumptions. In order to systematically evaluate such claims, the time has come to build a common framework for an empirical and intellectual unification of evolution and modern medicine. We review the emerging evidence and provide a support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 171 publications
1
35
0
Order By: Relevance
“…Such high molecular heterogeneity forms the foundation of diverse clinical outcomes and other cancer phenotypes, as well as makes hunting of cancer driver mutations very challenging (Heng, 2015). Our previous study showed that frequently observed cancer mutations are enriched at evolutionarily conserved positions (Dudley et al, 2012). Thus, evolutionary conservation estimated at the nucleotide level may help prioritize cancer driver mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Such high molecular heterogeneity forms the foundation of diverse clinical outcomes and other cancer phenotypes, as well as makes hunting of cancer driver mutations very challenging (Heng, 2015). Our previous study showed that frequently observed cancer mutations are enriched at evolutionarily conserved positions (Dudley et al, 2012). Thus, evolutionary conservation estimated at the nucleotide level may help prioritize cancer driver mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the rare and common variants associated with susceptibility to disease in modern populations have emerged through neutral selection processes [184]. However, there is increasing evidence to suggest that, following changes in environmental variables or human lifestyle, alleles that were previously adaptive can become “maladaptive” and associated with disease risk [12, 13, 29, 30, 105].…”
Section: Insight Into Rare and Common Diseases From Natural Selectionmentioning
confidence: 99%
“…However, distinguishing between neutral variants (i.e., those with little or no effect on phenotype) from variants associated with disease still remains a major challenge for both monogenic (Mendelian) and complex diseases . The current state‐of‐the‐art methods for diagnosing amino acid variants primarily employ evolutionary information obtained from multispecies sequence analysis in a variety of ways . While these methods have been used extensively, they often fail to correctly diagnose damaging variants at evolutionarily variable positions and neutral variants at highly conserved positions …”
Section: Introductionmentioning
confidence: 99%